Pharmacist Survey: Pharmacist Perception of Vancomycin Area Under the Curve Therapeutic Drug Monitoring. (April 2021) - Gregory, Eric R.; Burgess, Donna R.; Cotner, Sarah E.; VanHoose, Jeremy D.; Flannery, Alexander H.; Gardner, Brian; Autry, Elizabeth B.; Forster, Derek W.; Burgess, David S.; Wallace, Katie L.
Background: Evidence suggests the standard vancomycin trough goal of 15 to 20 mg/L for serious Staphylococcus aureus infections is associated with acute kidney injury, whereas appropriate monitoring of 24-hour area under the curve (AUC) may decrease nephrotoxicity. As a result, institutions have transitioned to AUC monitoring, the predictive pharmacokinetic/pharmacodynamic parameter of vancomycin to improve safety outcomes. However, this method may require increased pharmacist time and effort. Pharmacist perception of the practice change is largely unknown and warrants investigation. Methods: An electronic survey was disseminated via e-mail to pharmacists 5 months post-AUC implementation. Items of interest were focused on pharmacist perception, including quantity of patients monitored using AUC, justification of the practice change, differences in efficacy and safety, and changes in monitoring time requirements. Results: The pharmacist survey was distributed to 196 pharmacists and 84 responded (43% response rate). Eighty-one pharmacists had monitored patients using AUC methods. Sixty-nine percent of these respondents perceived the change to result in increased or slightly increased patient safety, 27% described no difference, and 4% stated safety was decreased or slightly decreased. Forty-two percent perceived the transition to result in increased or slightly increased efficacy, while 48% noted no difference and 10% responded that efficacy was decreased or slightly decreased. Pharmacists stated the creation of an institutional calculator decreased the time required to calculate AUC. Conclusion: After the change to AUC monitoring, pharmacists perceived improvements in safety outcomes while efficacy was at least similar if not increased.